Analisis Implementasi Manajemen Risiko Keuangan di Lembaga Pendidikan Pondok Pesantren Najaahaan - Salsabilla, Nazla Putri; Hidayat, Wahyu (STIT Fatahillah, 2025)
Financial risk management is an important element in maintaining the operational sustainability of educational institutions, especially in Islamic boarding schools, playing an important role in maintaining operational sustainability and quality of education. Najaahaan Islamic Boarding School as one of the pesantren-based educational institutions, faces challenges in financial management that can affect the smooth running of various educational and social activities. This research aims to identify and analyse the implementation of financial risk management at Najaahaan Islamic Boarding School, including the challenges faced and the strategies implemented to overcome these risks. This research uses a descriptive qualitative approach with data collection techniques in the form of observation and interviews conducted by researchers at the Najaahaan Islamic Boarding School. The results showed that the implementation of financial risk management at Najaahaan Islamic Boarding School has included risk identification, risk analysis, and risk mitigation. However, some weaknesses were found in terms of systematic risk documentation and monitoring. The main risks faced include income uncertainty, non-optimal fund management. To overcome this, the pesantren has implemented several strategies, such as diversification of income sources through productive business development. The conclusion in this study is that although the implementation of financial risk management at Najaahaan Islamic Boarding School has been running well, improvement efforts are needed in the aspects of strategic planning, use of information technology, and increasing the capacity of human resources